Screening of ARX, CDKL5 and STXBP1 gene mutations in Malaysian paediatric patients with early-onset epileptic encephalopathy by HRM technique - Jaafar, Ameerah (2015)
Gene mutation is one of the etiologies of early-onset infantile Epileptic Encephalopathy (EE), an age-dependant seizure in infants which leads to brain defects. Previous studies have shown that several genes namely, Aristaless-related homeobox (ARX), Cyclindependent kinase-like 5 (CDKL5) and Syntaxin-binding protein 1 (STXBP1) are responsible for the pathophysiology of the syndrome. This study aims to investigate the clinical association of Malaysian subjects with known and novel mutation as well as developing an efficient and effective genetic screening method. In this study, 3 mL blood was extracted from the consented patients and control. The DNA was extracted (QiAamp blood mini kit, Qiagen), quantified on purity (ND-1000 spectrophotometer, NanoDrop Technologies, Inc.) and integrity (0.8% gel electrophoresis) and screened using High Resolution Melting Analysis (QiAamp Type-It HRM kit, Qiagen).Peripheral blood was obtained and genomic DNA was purified (DNA purification Kit, Intron Biotechnology). A total of 11 primer pairs were designed flanking 13 known mutations in all genes of interest. ARX exonic region was also screened for known and novel mutation. PCR specificity and efficiency were optimized using conventional PCR, Quantitative Polymerase Chain Reaction (qPCR) and High Resolution Melting Analysis (HRMA). Different melting profiles which distinguished homozygotes and heterozygotes based on the shape and temperature shifting were generated. Profiles were clustered and compared with homozygous wild type reference control. Samples from varying clusters were purified and subjected to direct DNA sequencing. All assays were successfully established. All known mutations reported previously were not found in Malaysian patients with 100% confirmation by sequencing results. A variant could be screened in duplicates of all samples within 3 hours. Subsequently, ARX exonic regions were also sequenced using published primers. No mutation was found in all patients samples. Nevertheless, HRMA is a robust, simple, rapid, accurate, efficient and cost-effective tool of screening for early onset infantile EE patients gene mutation.